2022
DOI: 10.3389/fpubh.2022.992515
|View full text |Cite
|
Sign up to set email alerts
|

Development of occupational health culture scale: A study based on miners and construction workers

Abstract: Culture is an essential influence on effectiveness of workplace health promotion, which can promote occupational health protection behavior. The aim of this research was to develop and validate an occupational health culture scale available to Chinese workers. Occupational health culture scale (OHCS) was developed based on elements of health culture and safety culture in workplace. Nine techniques steps of scale development were used, including a 15-member expert group, 10 workers for cognitive interview, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The education and learning experience enabled workers to help to identify problems in the PAR process [ 52 , 53 ]. The previous studies found that the development of an occupational health culture among workers, creating awareness, establishing existing structures and procedures, and training by both needs assessment and evaluation together is crucial for successful training and long-term sustainable improvements [ 54 , 55 , 56 , 57 ]. The PAR process was the tool for key elements of BOHS development that corresponded to key elements of successful health and safety management, including policy, organization, planning, implementation, feedback to enhance BOHS, and auditing [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The education and learning experience enabled workers to help to identify problems in the PAR process [ 52 , 53 ]. The previous studies found that the development of an occupational health culture among workers, creating awareness, establishing existing structures and procedures, and training by both needs assessment and evaluation together is crucial for successful training and long-term sustainable improvements [ 54 , 55 , 56 , 57 ]. The PAR process was the tool for key elements of BOHS development that corresponded to key elements of successful health and safety management, including policy, organization, planning, implementation, feedback to enhance BOHS, and auditing [ 37 ].…”
Section: Resultsmentioning
confidence: 99%